2020
DOI: 10.1088/1367-2630/ab6a3b
|View full text |Cite
|
Sign up to set email alerts
|

Leaving bads provides better outcome than approaching goods in a social dilemma

Abstract: Individual migration has been regarded as an important factor for the evolution of cooperation in mobile populations. Motivations of migration, however, can be largely divergent: one is highly frustrated by the vicinity of an exploiter or defector, while other enthusiastically searches cooperator mates. Albeit both extreme attitudes are observed in human behavior, but their specific impacts on wellbeing remained unexplored. In this work, we propose an orientation-driven migration approach for mobile individual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Some previous studies have demonstrated how different migration preferences can have varied influence on the evolution of cooperation [ 40 ]. Inspired by this, in this study, we use and compare three different methods for selecting the migration destination.…”
Section: Modelmentioning
confidence: 99%
“…Some previous studies have demonstrated how different migration preferences can have varied influence on the evolution of cooperation [ 40 ]. Inspired by this, in this study, we use and compare three different methods for selecting the migration destination.…”
Section: Modelmentioning
confidence: 99%
“…Recently, [9] showed for the rst time that strategy-neutral migration triggered strategy oscillation in a two-strategy game even without the bridging of any transition strategies (states), thus de ning a novel oscillating behavior fundamentally different from the conventional cyclic dominance previously found in a game of at least three or more strategies. [10] studied the impact of varying migration preferences in promoting cooperation. They revealed the role of orientation-driven migration, where individuals prefer to move closer to their neighboring cooperators or favor escape away from their neighboring defectors.…”
Section: What Are Conditional Defector Strategies?mentioning
confidence: 99%
“…More precisely, they can collect a higher payoff individually if they defect, but if they all choose this strategy, then they will earn a smaller income than in the scenario when they cooperate. Interestingly, the conclusions are more subtle in terms of summary in the form of a simple message [21][22][23][24][25][26]. In some cases, the players' movement is proved to be harmful, while in other cases, it clearly becomes a mechanism for supporting cooperation.…”
Section: Introductionmentioning
confidence: 99%